COST ANALYSIS OF DIABETES MELLITUS - Elny Fitri; Tri Murti Andayani; Endang Suparniati (Faculty of Pharmacy, Universitas Gadjah Mada)
The high prevalence and complication of diabetes mellitus, as a chronic non-communicable disease, result a significant economicburden for the healthcare cost. This study aimed to calculate the total cost of illness, the effect of age, complication, the period andclass of inpatient on the real cost, the differences between the total of the real cost compared to the standard treatment cost of INACBGs for diabetic patients in the period of January until June 2014 in Dr. Sardjito Hospital, Yogyakarta. This research was a non-experimental analytic using retrospective approach. Research was conducted based on the hospital prespective by calculating the directmedical costs using a bottom-up approach. The samples included 1.396 patients with 1.935 episodes of care. The independentvariables included age, complications, length of hospitalization and treatment class, while the dependent variable was the real cost.The data was analyzed using the multiple regression statistic analysis. The result showed that the total cost of illness of diabetesmellitus was IDR 15.248.582,600. The multiple linear regression analysis showed that the complication and length of stay were the most influencing factors to the real costs of diabetic outpatients and inpatients. There was a difference between the realtotal cost and the standard treatment cost of INA-CBGs foroutpatient and inpatient with type 1 diabetic and also inpatient with type 2diabetes around IDR 46.511.644, IDR 100.647.901, and IDR 186.542.144 respectively in which the real total cost was lower than the INA CBG’s standard.Moreover, there was a difference in the real cost of outpatients with type 2 diabetic around IDR Rp -196.698.235 that higher than INA-CBG’s standard. Keywords: cost of illness, diabetes mellitus, INA-CBGs